Preexisting Rotator Cuff Tears as a Predictor of Outcomes in National Football League Athletes. (May 2016) - Gibbs, Daniel B.; Lynch, T. Sean; Gombera, M. Mustafa; Saltzman, Matthew D.; Nuber, Gordon W.; Schroeder, Gregory D.; Labelle, Mark; Hollett, Brian P.
Background: A preexisting rotator cuff tear may affect the draft status and career performance of National Football League (NFL) players. Hypothesis: Preexisting rotator cuff tears decrease a player's draft status, performance, and longevity in the NFL. Study Design: Retrospective cohort study. Level of Evidence: Level 3. Methods: Medical reports of prospective NFL players during the NFL Scouting Combine from 2003 to 2011 were evaluated to identify players with a previous rotator cuff tear. Athletes were matched to control draftees without documented shoulder pathology by age, position, year drafted, and round drafted. Career statistics and performance scores were calculated. Results: Between 2003 and 2011, 2965 consecutive athletes were evaluated. Forty-nine athletes had preexisting rotator cuff tears: 22 athletes underwent surgical intervention for their tear and 27 were treated nonoperatively. Those with a rotator cuff tear were significantly less likely to be drafted than those without a previous injury (55.1% vs 77.5%, P = 0.002). The 27 drafted athletes with preexisting rotator cuff tears started significantly fewer games (23.7 vs 43.0, P = 0.02) and played significantly fewer years (4.3 vs 5.7, P = 0.04) and significantly fewer games (47.1 vs 68.4, P = 0.04) than matched control athletes without rotator cuff tears. Conclusion: Athletes with a preexisting rotator cuff tear were less likely to be drafted and had decreased career longevity.